(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
Complex study on population level is carried out with allowing to define a present-day-state of model steppe species in the Regional Landscape Park “Donetskyi Kriazh”, which affords acontrolled anthropogenic press . It is revealed that cenopopulations maintain diversity of their age structure with belonging to normal mature and old types under such conditions.